Untamed Heart - Bill, Tony.; Slater, Christian; Marisa Tomei; Rosie Perez; Kyle Secor; Willie Garson; James Cada; Gary Groomes; Claudia Wilkens; Pat Clemons; Lotis Key; Vanessa Hart; et al. (USA Metro-Goldwyn-Mayer (MGM), 1993)
All of Caroline's boyfriends seem to leave her or cheat on her. On her way home from work two men try to rape Caroline...
All of Caroline's boyfriends seem to leave her or cheat on her. On her way home from work two men try to rape Caroline. An introverted man from her work, Adam, rescues her. Adam is an orphan and he is told that he's got a baboon's heart. Adam opens up to Caroline and together they make sense. Adam and Caroline are very happy together but the rapists try to get back at Adam and not everyone accepts an outcast like Adam.
Languages: English, French, German, Italian, Spanish Subtitles: English, French, German, Italian, Spanish, Dutch, Swedish, Norwegian, Danish, Finnish, Turkish
Keywords: Drama; Romance; Comedy